Pengaruh Atribut Produk, Persepsi Nilai, Pengalaman Konsumen terhadap Minat Beli Ulang Yang di mediasi Oleh Kepuasan Konsumen (Pada Pengguna Smartphone Xiaomi di Kelurahan Dinoyo, Malang) - Muhammad Ariasa; N Rachma; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract This study tries to analyze Product Attributes, Value Perceptions, Consumer Experiences, Product Attributes, and Repurchase Interests of Xiaomi Smartphone Users in Dinoyo District, Malang. "The sample in this study was smartphone users in Dinoyo District, Malang. The data collection techniques of this study were with questions. Data analysis used in this study was quantitative descriptive using a Likert scale, path analysis, t test, sobel test, and tests using the program Based on the results of data analysis, Perceived Value, Customer Experience has a significant influence on consumer satisfaction on xiaomi smartphone users in the Dinoyo District, and the Perception Value, Consumer Experience, and Customer Satisfaction variables have a significant influence on repurchases on xiaomi smartphone users at dinoyo District, The product attribute has no significant effect on customer satisfaction on xiaomi smartphone users in dinoyo District, and the product attribute variable is not significant on the repurchase interest for Xiaomi smartphone users in Dinoyo District, Malang.  Keywords: Product Attributes, Value Perception, Consumer Experience, Repurchase Interest, Consumer Satisfaction